Academic work and institutional diversity in Canada - Bégin-Caouette, Olivier; Béland, Sébastien; Karram Stephenson, Grace; Jones, Glen A.; Metcalfe, Amy Scott (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
The objective of this article is to determine if the work of full-time professors in Canada varies depending on the type of universities in which they are employed. A nonparametric comparison of multivariate samples based on data from the Academic Profession in the Knowledge Society (APIKS) survey was used to examine faculty perceptions of their academic work. The results show statistically significant, albeit minimal, differences between primarily undergraduate, comprehensive, and research-intensive institutions. This article confirms that, to a small extent, institutional diversity in Canada is mirrored in academic work, and argues that both vertical and horizontal forms of diversity may exist simultaneously depending on the relative value granted to specific academic activities.